Fitness Level Effect On The Grade-Point Average Of Physical Education Major Students - Wahyu Indra Bayu; Destriana Destriana; Achmad Richard Victorian; Herri Yusfi; Soleh Solahuddin (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
This study aims to perceive the relationship between physical fitness and the grade-point average. This study used a quantitative method with survey techniques with design correlation. The subjects of this study were 1st and 3rd-semester physical education college students with a total sample of 142 students (M: 97, F: 45). Random sampling was used as the sampling technique and TKJI (Indonesian Physical Fitness Test) was used as the instrument in this study was. The results show that 4 students (2,82%) were in very good, 68 students (47,89%) were in good, 58 students (40,85%) were in good fitness classification, 11 students (7,75%) were in less, and 1 students (0,7%) were in very less fitness classification. It means that the physical fitness of physical education college students mostly in good fitness classification. ANOVA was used to analyze the relationship between health-related physical fitness and grade-point average index.  The statistical test showsthat physical fitness has a positive correlationwith the grade-point average indexwith Sig (P-value) = 0,000 and 5% margin of error.Based on the t-test, the value of tcount (21,360)>ttable (2.12) which can be concluded that physical fitness affects the grade-point average index.